(untitled) (Journal of Indonesian Legal Studies, 2024)
This research aims to explore the dual role of generative AI technology in supporting human rights activism and gender equality. The primary issue addressed is how AI can empower individuals and organizations in advocating for human rights, while also posing risks such as the spread of misinformation and the perpetuation of bias. The methods used include case study analysis and literature review to understand the impact of AI in social and political contexts. The urgency of this research lies in the pressing need to develop ethical frameworks that safeguard human rights amid rapid technological advancements. The novelty of this study stems from its interdisciplinary approach, combining technology, human rights, and gender equality, while highlighting the philosophical and ethical challenges that arise alongside AI development. The findings of the research indicate that AI holds significant potential to enhance the visibility of human rights issues through more effective social media campaigns and compelling data presentation. However, the study also identifies substantial risks, including information manipulation and biases that could harm certain groups. The conclusion emphasizes the importance of creating strategies that maximize the benefits of AI while minimizing its risks. Thus, this research contributes to efforts to create an AI-driven future that not only supports human rights but also promotes gender equality, and it encourages further discussions about the boundaries between humans and machines in the context of these rights.